Internet gaming disorder and aggression: A meta-analysis of teenagers and young adults - Li, Shunyu; Wu, Zhili; Zhang, Yuxuan; Xu, Mengmeng; Wang, Xiaotong; Ma, Xiaonan (Frontiers in Public Health, 2023)
Background and aims Internet gaming disorder (IGD) and aggression (AG) are widespread phenomena around the world. Numerous studies have explored the relationship between the two but findings from such studies are inconsistent. The meta-analysis aimed to evaluate the relationship between IGD and AG as well as identify the variables moderating the relationship. Method Studies investigating the relationship between IGD and AG were searched using selected terms to identify studies published from 1999 to 2022 on CNKI, Wanfang Data, Chongqing VIP Information Co., Ltd. (VIP), Baidu scholar, ProQuest dissertations, Taylor & Francis, Springer, Web of Science, Google Scholar, Elsevier Science (Science Direct), EBSCO, and PsycINFO. The identified studies were pooled and analyzed. Results A total of 30 samples comprising 20,790 subjects were identified. Results showed that there was a moderate relationship between IGD and AG (r = 0.300, 95%CI [0.246, 0.353]). Moderator analysis revealed that the relationship between IGD and AG was moderated by the region, age, and survey year. Conclusion This meta-analysis indicated that people with a higher level of IGD might show more aggression, and people with more aggression might have a higher level of IGD. The correlation coefficient between IGD and AG was significantly higher in Asia than in Europe, higher in primary school than in middle school and university, and higher by increasing year. Overall, our findings provide a basis for developing prevention and intervention strategies against IGD and AG. Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022375267, 42022375267.